Hubungan Pengetahuan Ibu Hamil dengan Pemanfaatan Buku Kia di Puskesmas Teras Terunjam Kabupaten Mukomuko - Emma Carolina Situmorang; Ronalen Br. Situmorang; Desi Aulia Umami (Jurnal Pakar Kesehatan, 2026)
Indonesian Demographic and Health Survey (SDKI) Maternal Mortality Rate to date reaches 183 per 100.000 live births. The Ministry of Health (Kemenkes) recorded that as many as 4.129 mothers in Indonesia died in 2023. That number increased by 1.24% percent compared to 2022 which was 4005 people. The main causes of maternal death include high blood pressure during pregnancy (pre-eclampsia and eclampsia), hemorrhage, postpartum infection, and unsafe abortion (Kemenkes, 2023). The purpose of this study is to determine the relationship of pregnant mothers' knowledge with the utilization of the MCH Handbook (KIA) at Teras Terunjam Health Center, Mukomuko Regency. In Methods the type of research used quantitative with a sample size of 30 pregnant mothers. The independent variable is pregnant mothers' knowledge and the dependent variable is utilization of the KIA handbook. The data analysis of this study used the Chi Square statistical test (α=0.05). The authors' research results show that the majority of respondents, namely 19 (63.3%) rspondents, have sufficient knowledge at Teras Terunjam Health Center. The majority of respondents, namely 20 (66.7%) respondents, have poor utilization of the KIA handbook at Teras Terunjam Health Center. The chi square test result found that there is a relationship between pregnant mothers' knowledge and the utilization of the KIA handbook at Teras Terunjam Health Center, Mukomuko Regency with p=0.000 which means p <0.05, namely H1 is accepted. The conclusion in this study is that there is a relationship between pregnant mothers' knowledge and the utilization of the KIA handbook at Teras Terunjam Health Center, Mukomuko Regency. Counseling needs to be carried out for pregnant mothers at BPM, health centers, hospitals and health service places to increase pregnant mothers' knowledge in the utilization of the KIA handbook and be beneficial for mothers and babies up to 5 years.